Legal Aspects of Procurement Accountability in West Papua, Indonesia - Korwa, Jimmi; Roberth KR Hammar; Imanuel I. R. Hammar (Golden Ratio of Law and Social Policy Review, 2025)
Government procurement of goods and services strategically supports national development, including in regions with special characteristics such as West Papua Province. Even though the legal framework for procurement has been regulated normatively through Presidential Regulation Number 12 of 2021, implementing accountability principles in West Papua still faces various challenges. This study aims to analyze the implementation of the principle of accountability in the procurement of goods and services in West Papua from the perspective of Indonesian positive law, as well as assess the effectiveness of its application in a complex geographical and social context. The theoretical approaches used include public accountability theory, sound governance principles, and John Rawls's theory of legal justice. The study results show a gap between legal norms and practice in the field, which is characterized by weak supervision, low human resource capacity, and minimal community participation. This condition indicates the need to strengthen the legal supervision system and policy reformulation that is adaptive to regional specificities.